Cesium Concentration Spatial Distribution Modeling by Point Cumulative Semivariogram - Kuelahci, Fatih; Sen, Zekai; Kazanc, Sefa (Springer Science and Business Media LLC, 2008)
The theoretical basis of the proposed technique is the cumulative variation of 137Cs measurements’ squared-differences between a reference and other sites. The change of the cumulative squared-differences with distance from the reference site is referred to as the point cumulative semivariogram (PCSV), which provides appropriate measure of cumulative similarity. Inspection of individual experimental PCSV provides local interpretation about the 137Cs radioactivity concentration around each site, whereas collective inspections provide possibility for grouping similar sites and hence identifying homogeneous sub-areas within the study area. It is also possible to prepare 137Cs radioactivity concentration maps based on pre-specified distances in each experimental PCSV, which lead to similarity levels. Such maps provide appreciation of 137Cs radioactivity concentration regional dependence in Keban Dam Lake, Turkey. Apart from the individual PCSV interpretations, the whole lake is divided into four distinctive classes.